Economic Relations between Italy and Albania 1993 - 2000. - Marko, Juliana (Academicus, 2012)
The history of economic relations between Italy and Albania is a typical example of asymmetric relationship between two countries with geographic proximity but with very different dimensions. The importance of this bond is essential for Albania, as Italy is our greatest economic and trade partner, but also from the Italian perspective these relationships have a greater weight than we might expect given the size of the Albanian economy, due to geographical proximity and preferential relations between the two countries. The relations with Albania are included in the broader context of the Italian policy in the entire Balkan region as these countries transition towards free market economic system is of great importance for the European integration processes. Since 2000, the economic cooperation has grown, but its features (trade balance deficit, restricted investment areas, à façon industries, etc.) still persist. This paper intends to highlight the strengths and drawbacks of Italian - Albanian economic relations in its early stages from 1990 to 2000.